Karakteristik tepung nanas varietas queen (Ananas comosus L.Merr) termodifikasi metode foam mat drying - Isnawati Nurjannah; Cahyaning Rini Utami (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Ananas comosus L. Merr in Indonesia has a very large production rate but the shelf life is relatively short. Alternatives increase the shelf life of pineapple fruit made in the form of flour. The quality of pineapple flour is determined by the drying method so that modifications to the method using foam mat drying with variations in the addition of maltodextrin and tween 80. This study aims to find out the effect of increasing the concentration of maltodextrin and tween 80 on the physicochemicals of pineapple flour so that pineapple flour is obtained that has good characteristics. The research method using faktorial RAK consists of 2 factors. The first factor of maltodextrin concentration (10%,15%,25%) and the second factor of tween 80 percentage (0.1%, 0.3%) repeated 3 times resulted in 18 attempts. Analysis of physicochemical data is analyzed using ANOVA statistics. If it's a real difference in the Tukey test. Organoleptic testing uses friedman's method. The best treatment of physicochemical and organoleptic analysis uses the Effectiveness Index method. The best research results of pineapple flour on physicochemical and organoleptic content are found in N3T2 treatment (maltodextrin 25% and tween 80 0.3%) with characteristics: antioxidant activity 45.57 mg/ml, vitamin C levels 92.45 mg/100g, water content 5.98%, ash content 0.61%, color intensity L 58.49, color a* 29.30 and color b* 26.90 and organoleptic color 4.33 (likes), texture 2.83 (sufficient).